HIV and reproductive healthcare in pregnant and postpartum HIV-infected women: adapting successful strategies. (August 2016) - Rimawi, Bassam H; Smith, Somer L; Badell, Martina L; Zahedi-Spung, Leilah D; Sheth, Anandi N; Haddad, Lisa; Chakraborty, Rana
Linkage and retention in care for many HIV-infected women in the postpartum period is suboptimal, which compromises long-term virologic suppression and the HIV Care Continuum. Efforts are needed to improve individual outcomes by addressing transitions in care. We summarize some successful strategies to engage and retain HIV-infected women in care during the postpartum period.